The Contribution of the Indonesian Woman Constitutional Justice in Achieving the Sustainable Development Goals - Fu'adah, Akhyaroni (Media Syari'ah, 2024)
This study explores the role of woman as constitutional judges for the realization of the sustainable development goals (SDGs). One of the goals of the SDGs is gender equality, one such as ensuring effective participation for women as public officers, including as constitutional judges. However, in fact, the number of female constitutional judges are much less than male constitutional judges in Indonesia, due to patriarchy and Islamic paradigms. Woman’s perspective is substantial thing in decision making, though. To comprehend the issue, this research will examine the election and the role of women constitutional judges in the realization of the SDGs. The statutory approach was adopted to study laws and regulations, and the comparative approach was implemented to deeply understand the comparison between Indonesia’s laws and Islamic perspectives relating to the status of woman as judge. Secondary data from literature review and library research support an analysis for a deeper understanding of the concept of requirements to be a Constitutional Justice. The finding of this research implies that there are different opinions in Islam perspective, even the contemporary scholars argue that woman can be a judge, including in constitutional justice. This study emphasizes that anybody can be a judge, if they can fulfill the requirements: having integrity and impeccable personality, be just, be a statesman/stateswoman mastering the constitution and constitutionalism and does not concurrently hold a public office. Consequently, it will encourage decisions that consider women's rights to realize sustainable development goals.